THE EFFECT OF ENTREPRENEURIAL LITERACY ON ENTREPRENEURIAL INTENTION THROUGH SELF-EFFICACY AS A MEDIATOR VARIABLE - Subandi, Subandi; Murwani, F. Danardana; Maharani, Satia Nur (International Journal of Business, Law, and Education, 2023)
Business is an action that has to be completed in the ongoing period of globalization and industrialization, especially after the Coronavirus. The development of the Indonesian state through its entrepreneurship can compete and even outperform other developing countries that have more entrepreneurs. This research uses a quantitative approach with Partial Least Squares structural equation modeling (PLS-SEM) to predict and confirm the given hypothesis. This study used Google Forms for data collection on Madrasah Aliyah students in Mojokerto Regency. Respondents in this study were 356 respondents from the three schools used as research objects. The results showed that Entrepreneurial Literacy can explain Self-efficacy and Entrepreneurial Intention. Furthermore, Entrepreneurial Literacy will have more influence on Entrepreneurial Intention, if strengthened by Self Efficacy as a mediator variable.